Gender‐neutral donor deferral policies: experience in Argentina implementing individual risk‐assessment policies - Blanco, Sebastián; Carrizo, Luis Horacio; Moyano, Rolando Walter; Mangeaud, Arnaldo; Gallego, Sandra Verónica (Vox sanguinis, 2020)
Background In Argentina, with the aim of moving to a safe supportive and inclusive National Blood System, in September 2015 the Ministry of Health stipulated that eligibility criteria for blood donation should only take into account the so‐called 'risk practices', focusing on a 'gender‐neutral' policy. The aim of this study is to demonstrate the impact of such regulation on the prevalence of STI in the population of blood donors in Argentina, through the analysis of the scientific evidence obtained from 174 074 donors from a large central region of the country, focused on a regional Blood Bank for a 6‐year period (pre‐ and post‐entry into force of the regulations). Materials and Methods To analyse the evolution of prevalence rates of STI, two periods of 3 years each were evaluated: The first period (P1) lasted from 16 September 2012 to 15 September 2015 (prior to the entry into force of the law) and the second one (P2) from 16 September 2015 to 15 September 2018 (after the entry into force of the law). Results A total of 82 838 subjects were enrolled in P1 and 91 236 in P2. The results show a significantly lower prevalence of HCV (P = 0·029), HBV (P = 0·028) and syphilis (P = 0·001) in P2, while no difference was observed for HIV infection (P = 0·60). Conclusion This study evidenced that the implementation of a 'gender‐neutral' policy based on individual risk‐assessment deferral criteria maintained the safety of blood supply and decreased the prevalence of STI among blood donors.